'He also has the right to be who he is … '. An exploration of how young people socially represent autism. Issue 7 (3rd July 2017) - Fondelli, Thomas; Rober, Peter
ABSTRACT: An increasing number of young people are being confronted with the concept of autism. Some of them know someone who has been diagnosed as autistic. Others learn about the concept through different forms of media. Nevertheless, little research has been conducted into the meaning which young people give to the concept. In this study, we explored by means of focus groups how a number of young people try to understand what autism is and how they should or want to relate to it. A thematic analysis resulted in three interconnected central themes: (1) Autism is Different; (2) The Different One and the others; and (3) Watch out: the diagnosis of autism actually 'makes' a person Different. Although our participants represented autism as a fundamental form of being different, they also reflected on how a diagnosis does not just identify a reality, but also creates a reality. To them, autism is different, but the diagnosis of autism also makes a person different. Based on these results, attention is drawn to the risks of class or group discussions focusing exclusively on what autism is, as such discussions may reinforce the representation that someone with autism is fundamentally different, while possibly spurring exclusion.